Digitizing Geometric Ornaments of the Bandung Grand Mosque for Cultural Preservation - Putri, Ghaida Nasya; Atik, Saftiyaningsih Ken (Departement of Architecture, Universitas Islam Indonesia, 2026)
This research explores the preservation of decorative motifs in the Bandung Grand Mosque through digitization as an effort to safeguard Islamic and Sundanese cultural heritage. Although the mosque has been widely discussed in architectural studies, systematic documentation of its ornaments is still limited. This study addresses that gap by digitizing geometric motifs and analyzing their structural complexity. A qualitative approach with a comparative strategy was applied, involving literature review, field observation, and digitization using CorelDRAW software. The findings show that geometric ornamentation dominates the mosque with varying levels of complexity depending on its line intersections and the number of geometric repetitions or tessellations. The study produces a publicly accessible digital catalog that preserves the accuracy of ornamental forms and supports their reuse in education, design, and cultural conservation. The results demonstrate that digitization is an effective method for documenting traditional ornaments while opening new possibilities for contemporary motif development.